2018
DOI: 10.1038/s41598-018-24208-2
|View full text |Cite
|
Sign up to set email alerts
|

Disposable all-printed electronic biosensor for instantaneous detection and classification of pathogens

Abstract: A novel disposable all-printed electronic biosensor is proposed for a fast detection and classification of bacteria. This biosensor is applied to classify three types of popular pathogens: Salmonella typhimurium, and the Escherichia coli strains JM109 and DH5-α. The proposed sensor consists of inter-digital silver electrodes fabricated through an inkjet material printer and silver nanowires uniformly decorated on the electrodes through the electrohydrodynamic technique on a polyamide based polyethylene terepht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Microbes in drinking water are generally detected through conventional microbial culturing, ELISA or PCR methods in central laboratories which are generally slow and/or labor intensive (once again similar to POCT and food analysis). Disposable sensors can be used to either sense the presence of whole microbes or their genetic materials in samples of water to quantify their concentrations at the point of need. Disposable microbial sensors may employ antibodies, bacteriophages or nucleic acids for capture and recognition of specific microbes.…”
Section: Fields Of Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbes in drinking water are generally detected through conventional microbial culturing, ELISA or PCR methods in central laboratories which are generally slow and/or labor intensive (once again similar to POCT and food analysis). Disposable sensors can be used to either sense the presence of whole microbes or their genetic materials in samples of water to quantify their concentrations at the point of need. Disposable microbial sensors may employ antibodies, bacteriophages or nucleic acids for capture and recognition of specific microbes.…”
Section: Fields Of Applicationmentioning
confidence: 99%
“…Disposable microbial sensors may employ antibodies, bacteriophages or nucleic acids for capture and recognition of specific microbes. Paper, metals and polymers are commonly used for the construction of open‐ and closed‐channel microfluidic devices which may use electrochemical, colorimetric or luminescent methods of transduction for quantification. Regardless of the method of sensing, the number of microbes in a sample of water may be too low.…”
Section: Fields Of Applicationmentioning
confidence: 99%
“…Although the design and construction of the sensing elements present technical challenges, having the ability to directly observe the physical presence of an analyte without secondary probes or assay reagents allows for the rapid, unperturbed measurement of samples. In a recent example, Ali et al (120) demonstrated the use of silver nanowires to substantially enhance the sensitivity of contact-based impedance sensing. Using the transient response of the sensing element, the authors could differentiate between three species of bacterial pathogens within 8 min of exposure to the sample.…”
Section: Biosensor-based Approaches For Rapid Pathogenidentification mentioning
confidence: 99%
“…The prominent noncontact printing techniques include slot-die coating, electrohydrodynamics, and inkjet printing. The noncontact printing techniques have received greater attractions due to their distinct capabilities such as simplicity, affordability, speed, adaptability to the fabrication process, reduced material wastage, high resolution of patterns, and easy control by adjusting few process parameters [6,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%